2012
DOI: 10.1007/978-1-4614-5037-5_8
|View full text |Cite
|
Sign up to set email alerts
|

RecQ Helicases: Conserved Guardians of Genomic Integrity

Abstract: The RecQ family of DNA helicases is highly conserved throughout -evolution, and is important for the maintenance of genome stability. In humans, five RecQ family members have been identified: BLM, WRN, RECQ4, RECQ1 and RECQ5. Defects in three of these give rise to Bloom's syndrome (BLM), Werner's syndrome (WRN) and Rothmund-Thomson/RAPADILINO/Baller-Gerold (RECQ4) syndromes. These syndromes are characterised by cancer predisposition and/or premature ageing. In this review, we focus on the roles of BLM and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
146
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 119 publications
1
146
0
Order By: Relevance
“…Both the yeast Sgs1 helicase and its mammalian ortholog, BLM, carry out numerous functions in the repair of DSBs and replication forks and thus represent a key node to maintain genome integrity (Larsen and Hickson 2013). However, these helicases can perform both pro-and anti-recombinogenic tasks, often acting on similar substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the yeast Sgs1 helicase and its mammalian ortholog, BLM, carry out numerous functions in the repair of DSBs and replication forks and thus represent a key node to maintain genome integrity (Larsen and Hickson 2013). However, these helicases can perform both pro-and anti-recombinogenic tasks, often acting on similar substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous recombination (HR) is a crucial repair pathway in mitotic cells and involves the use of similar sequences as a template for accurate repair (Paques and Haber 1999). The yeast RecQ helicase Sgs1 contributes significantly to HR (Larsen and Hickson 2013). Sgs1 forms a heteromeric complex with the type IA topoisomerase Top3 (Gangloff et al 1994;Bennett et al 2000;Oakley et al 2002) and the OB-fold-containing protein Rmi1 (Chang et al 2005;Mullen et al 2005), a complex named STR (Sgs1-Top3-Rmi1) (Ashton and Hickson 2010).…”
mentioning
confidence: 99%
“…In contrast, during dissolution (B), each strand engaged in the dHJ is reassociated with its original complementary strand, preventing exchange of genetic material between the two homologous sequences (and hence generating exclusively noncrossover products because they are better characterized in terms of their interactions with dHJs (for a detailed review on RecQ of E. coli, see Nakayama 2005). Nevertheless, it is clear that the malfunction of a RecQ helicase causes genome instability in all organisms (for review, see Chu and Hickson 2009;Bernstein et al 2010;Larsen and Hickson 2013). In particular, a consistent observation in recQ helicase mutants is an increase in the frequency of crossing-over, which is generally detected by scoring the level of sister chromatid exchanges (SCEs) or loss of heterozygosity between homologs.…”
Section: Background On Recq Helicasesmentioning
confidence: 99%
“…RecQ helicases are referred to as conserved guardians of genomic integrity (69) and are reported to be involved in multiple pathways for the maintenance of genomic stability, including HR (69-73). As was shown for its previously studied ortholog in S. solfataricus (Sso0112 or Hel112) (44,45), we demonstrated that Saci_1500 shows typical RecQ-like DNA binding and unwinding activities.…”
Section: Figmentioning
confidence: 99%